INTERFERENSI BAHASA ASING DALAM TUTURAN BAHASA INDONESIA MAHASISWA UNIVERSITAS PERADABAN - Prameswari, Ikhya Aulia (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2025)
This study aims to identify and analyze the forms and factors causing foreign language interference in the Indonesian speech of students at Universitas Peradaban. Foreign language interference, particularly from English and Arabic, often appears in students' verbal communication and has the potential to influence the structure and rules of normative Indonesian. This research is motivated by a common phenomenon in academic environments where students are accustomed to using foreign terms in their daily lives, both in formal and informal contexts, thereby triggering linguistic shifts and deviations in their native language. The research method used is descriptive qualitative, employing data collection techniques such as participatory observation, semi-structured interviews, and documentation of students' speech recordings from various faculties. The data were then analyzed using a linguistic analysis approach by classifying the forms of interference into phonological, morphological, syntactic, and lexical aspects. The results of the study indicate that the most dominant interference occurs in the lexical aspect, where many English words or phrases are used directly without translation, such as “deadline,” “submit,” or “mute”. Additionally, there were syntactic deviations due to the influence of foreign sentence structures. The main factors causing interference included the habit of using foreign languages in lecture materials, the influence of digital media, and the perception that using foreign languages reflects a higher level of intellectuality. The conclusion of this study confirms that foreign language interference in student speech is not only a linguistic phenomenon but also reflects the social and cultural dynamics within the academic community. Therefore, efforts to strengthen awareness of proper and correct Indonesian language use in higher education settings are necessary to preserve the national language identity.